Space and Transformation: The Struggle for Architecture in Post Apartheid South Africa - Low, Iain (Afrika Focus, 2019)
The title and this essay, ‘Space and Transformation – the struggle for architecture in post-apartheid South Africa’ derive from the 2nd Annual Nelson Mandela Lecture delivered in Ghent in 2015. Its source as my topic is located in the intersection of three interrelated trajectories. The most obvious is the issue of my disciplinary grounding and the locus of intellectual thought, that of architecture and the complexity associated with the production of space, particularly under conditions of change. The other is the life work and philosophical teaching of this extraordinary man Nelson Rolihlahla Mandela and the third is the condition of the world, and South Africa in particular, as we experience it today at what appears to be this unique historic intersectional moment of globalization and expansive tech- nological shift within our nations’ democratic emergence. The essay draws on texts derived from other disciplines, such as literature and philosophy, particularly those that have relevance to conditions of the South, but resorts to the spatial disciplining associated with design. In so doing it reflects on architectural projects produced during the first decades of democratic rule. Most of these projects fall within the realm of human settlement, and have been selected in order to demonstrate transformation relative to the lived reality of ordinary South Africans, especially those marginalised and dispossessed by apartheid legislation. A semi-structured longitudinal analysis has been conducted so as to reflect on the relations between the agency of design and the instrumentation of architecture as practice in determining spatial transformation. KEYWORDS: MANDELA, SPACE AND TRANSFORMATION, POST-APARTHEID, RE-RITING ARCHITECTURAL TYPE, DESIGN AGENCY, LAND, HOUSING, SOCIO-SPATIAL INFRASTRUCTURE, RE-BUILDING COMMUNITY.